Promoting Personnel Performance Motivation Nakhon Ratchasima Provincial Local Government Promotion Office: Promoting Personnel Performance Motivation Nakhon Ratchasima Provincial Local Government Promotion Office - Makar, Bunviphar; Phuthiphongchaicharn, Thanyarat; Wichairam, Sathaporn (RATANABUTH JOURNAL, 2024)
The objectives of this research are 1) to study the level of motivation in the performance of personnel of the Nakhon Ratchasima Provincial Local Government Promotion Office. 2) To compare the opinions on promoting motivation of Nakhon Ratchasima Provincial Local Government Promotion Office personnel according to personal factors such as gender, age, and education. 3) To study opinions and other suggestions to promote the motivation of Nakhon Ratchasima Provincial Local Government Promotion Office personnel. Using a mixed research model, namely 1) quantitative research, the population in the study was personnel of the Nakhon Ratchasima Provincial Local Government Promotion Office. 90 people using a questionnaire. The statistics used in the data analysis include percentages, averages, standard deviations, and other factors. T value testing and one-way comparative analysis of variance. The results showed that the overall motivation for work was very high. When looking at each side, it was found that all aspects were also at a very high level. 2) To compare the opinions and motivations of Nakhon Ratchasima Provincial Local Government Promotion Office personnel to classify them according to personal factors. It was found that the level of motivation in overall and individual aspects was not different. 3) Comments and suggestions on the motivation of the personnel of the Nakhon Ratchasima Provincial Local Government Promotion Office. It was found that self-development should be promoted. In terms of knowledge and skills necessary for the job, such as legal knowledge. Regulations, Rules, and Guidelines for Local Administration on an ongoing basis. Communication skills should be improved. Learn new technologies to increase work efficiency, including the Nakhon Ratchasima Provincial Local Government Promotion Office to improve the welfare system to be in line with the times. Create a working environment to encourage civil servants to work effectively.